ISO 14001 Compliance with Environmental Regulations by the Malaysian Electrical and Electronics Industry - Indra, Harjeet Kaur (1999)
This study focuses on voluntary environmental initiatives through the implementation of the ISO 14001 Environmental Management Standard (EMS) particularly by the electrical and electronics industry in Selangor. The standard is expected to upgrade an organisation's overall environmental performance and could also pose trade barriers if used as a precondition for international trade as experienced with the ISO 9000 Quality Management Standards. The ISO 1400 1 EMS variable, several organisation characteristics and regulatory enforcement activity were included into the compliance model to determine factors contributing to non-compliance. Data were obtained through the use of the mail-questionnaire method and analyzed using the maximum likelihood technique. The Shazam econometric program was used for the estimation.Though constrained by small sample size, results obtained have a priori expected signs at 5 and 1 percent level of significance respectively. Non-compliance is likely to be present among organisations that are generally older, incurring high compliance costs, obtaining external funds and receiving less regulatory enforcement. Profit, plant ownership and the ISO 14001 EMS standard were insignificant. The ISO 1400 1 EMS standard coefficient though positive is insignificant and thus provides insufficient evidence for enhancing an organisation's environmental compliance. Nine percent of respondents had difficulty in accessing international markets confirming that the standard is being used as a precondition for doing business. In summary, findings show organisation characteristics and regulatory enforcement activity influences an organisation decision to comply with environmental regulations.